Measurement and analysis of blast fragmentation : workshop hosted by FRAGBLAST 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November 2012 /: workshop hosted by FRAGBLAST 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November 2012. (©2013) - Unknown
No abstract available